Level of lactate in amniotic fluid and its relation to the use of oxytocin and adverse neonatal outcome. (15th October 2013) - Wiberg‐Itzel, Eva; Pembe, Andrea B.; Wray, Susan; Wihlbäck, Anna‐Carin; Darj, Elisabeth; Hoesli, Irene; Åkerud, Helena
Abstract Objective To assess whether the frequency of adverse neonatal outcome at delivery is related to the level of lactate in amniotic fluid and to the use of oxytocin. Design Prospective observational study. Setting Soder Hospital, Stockholm, Sweden. Population Seventy‐four women in active labor with a gestational age ≥36 weeks and mixed parity. Methods Levels of lactate in amniotic fluid were analyzed bedside from an intrauterine catheter every 30 min during labor. Deliveries were divided into groups with and without oxytocin. Main outcome measures The frequency of adverse neonatal outcome at delivery. Result Of the deliveries 13.5% (10/74) concluded with an adverse neonatal outcome. The levels of lactate in amniotic fluid increased during labor, more so in deliveries where oxytocin was used. In the group with an adverse neonatal outcome, the level of lactate in amniotic fluid was significantly higher in the final sample before delivery (p = 0.04). In 18 deliveries, stimulation with oxytocin was temporarily halted for at least 30 min due to overly stimulated labor contractions. A decreasing level of lactate in amniotic fluid was shown within a median 5%/30 min. In the group where the administration of oxytocin was halted, there was no adverse neonatal outcome. Conclusion The frequency of adverse neonatal outcome was associated with the level of lactate in amniotic fluid and with the use of oxytocin. The level of lactate in amniotic fluid may be an additional valuable tool when oxytocin is administered during labor.